2008
DOI: 10.1117/12.796174
|View full text |Cite
|
Sign up to set email alerts
|

An explosives detection system for airline security using coherent x-ray scattering technology

Abstract: L-3 Communications Security and Detection Systems (SDS) has developed a new system for automated alarm resolution in airline baggage Explosive Detection Systems (EDS) based on coherent x-ray scattering spectroscopy. The capabilities of the system were demonstrated in tests with concealed explosives at the Transportation Security Laboratory and airline passenger baggage at Orlando International Airport. The system uses x-ray image information to identify suspicious objects and performs targeted diffraction meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In homeland security applications, Madden et al [5] and Harding [22] proposed systems for explosives detection in suitcases that first acquired a transmission image of the suitcase, followed by an X-ray diffraction image of objects that raised suspicion in the transmission image. They argued that X-ray diffraction provided orthogonal information to transmission measurements and therefore X-ray diffraction could be used as a second automatic screening in order to reduce the number of bags that needed to be manually opened and inspected.…”
Section: Potential Applications Of X-ray Scatter Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In homeland security applications, Madden et al [5] and Harding [22] proposed systems for explosives detection in suitcases that first acquired a transmission image of the suitcase, followed by an X-ray diffraction image of objects that raised suspicion in the transmission image. They argued that X-ray diffraction provided orthogonal information to transmission measurements and therefore X-ray diffraction could be used as a second automatic screening in order to reduce the number of bags that needed to be manually opened and inspected.…”
Section: Potential Applications Of X-ray Scatter Imagingmentioning
confidence: 99%
“…The concept of X-ray scatter imaging has been investigated for material identification based on coherent scatter information for medical [1][2][3] and homeland security [4,5] applications. These studies have shown that scattered X-rays can provide higher signal-to-noise ratios (SNR) in identifying certain tissue types (medical) and sensitive materials (homeland security) than is currently possible using transmitted X-rays.…”
Section: Introductionmentioning
confidence: 99%
“…It has been illustrated that the Compton cross section is suppressed at small angles in literature [15]. Taking the complex detection condition of human body into consideration, 3-6°are chosen as suitable angles and the spectra at different angles are shown in the below Fig.…”
Section: Experimental Condition Selection and Data Acquisitionmentioning
confidence: 99%
“…The SVM has been mentioned to identify airline baggage for two class problem [15]. However, a multi-classifier of SVMs is necessary for identifying various kinds of material.…”
Section: Introductionmentioning
confidence: 99%
“…Madden et al 15 developed a coherent x-ray scattering CT system to enhance screening of explosives and other illegal materials. They showed that their system significantly reduced the rate of false alarms over traditional radiographic techniques.…”
Section: Introductionmentioning
confidence: 99%